FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOBILISASI DINI PADA PENYEMBUHAN LUKA OPERASI SECTIO CESAREA DI MAYAPADA HOSPITAL TANGERANG - Nurtriasmi Evalinda; Suraya Suraya; Retno Andriati; Ayu Rahayu; Dyna Meilolita; Marsondang Situmeang (CV. Denasya Smart Publisher, 2025)
Many studies reveal that the increasing number of deliveries with Sectio Caesarea (SC) surgery is directly proportional to the increase in the incidence of postoperative wound infections. Factors related to post SC wound healing are age, nutrition, parity, family support, mobilization early. This study was to analyze the factors associated with wound healing post surgery SC. Correlation descriptive design with cross sectional. The population is 215 people, the total sampling method is 61 people. Data collection used a questionnaire, analyzed using the Chi-square test, presented in tabular form. The majority of age categories aged 20 -35 years (70.5%), good nutrition (78.9%), elementary education level 23 (37.7%), low parity (73.8%), comorbid diseases (50.8%) , Good family support (73.8%), good early mobilization (72.1%), good wound healing (73.8%). It is known that there is a significant relationship between 6 factors (independent variables) with post SC wound healing with P values as follows: age = 0.009, nutrition = 0.003, parity = 0.000, comorbidities = 0.000, family support = 0.000 and early mobilization = 0.000, where P value ≤ 0.05. There is a significant relationship between factors associated with post SC wound healing